Modal-space reference-model-tracking fuzzy control of earthquake excited structures. (6th January 2015) - Park, Kwan-Soon; Ok, Seung-Yong
Abstract: This paper describes an adaptive modal-space reference-model-tracking fuzzy control technique for the vibration control of earthquake-excited structures. In the proposed approach, the fuzzy logic is introduced to update optimal control force so that the controlled structural response can track the desired response of a reference model. For easy and practical implementation, the reference model is constructed by assigning the target damping ratios to the first few dominant modes in modal space. The numerical simulation results demonstrate that the proposed approach successfully achieves not only the adaptive fault-tolerant control system against partial actuator failures but also the robust performance against the variations of the uncertain system properties by redistributing the feedback control forces to the available actuators. Highlights: We propose an adaptive modal-space reference-model-tracking fuzzy control for earthquake-excited structures. The proposed method can guarantee outperforming robust performance as well as adaptive fault-tolerant control. The proposed approach is able to effectively redistribute the feedback control forces to the post-seismic available actuators. The proposed approach utilizes a few of the dominant modal responses in practical view point.